Collaboration in construction research – A key to developing effective postdoctoral strategies and research focused university culture - Preece, Christopher Nigel; Abdul Rashid, Khairuddin; Hasan, Sharina Farihah; Padfield, Rory (2011)
This paper focuses on how collaboration in research is a key to more effective personal postdoctoral strategies for new and inexperienced construction academics and can help to ensure the development of more research focused university cultures. It also identifies an 11 point plan for new and inexperienced academics which will have benefits for both the individual researcher and the institution. The methodology includes literature search and a case-study; MoU between Kyoto University and International Islamic University Malaysia. The case study is an example of successful research collaboration that leads towards postdoctoral training. A model is proposed to serve as a basis for future collaboration.